CHEMICAL AND FATTY ACIDS COMPOSITION OF RUMP CAP FROM YOUNG BULLS FED PROTECTED OR UNPROTECTED OILS - Oliveira, Emanuel Almeida de [UNESP]; Moraes Sampaio, Alexandre Amstalden [UNESP]; Henrique, Wignez; Pivaro, Thiago Martins [UNESP]; Rosa, Bruna Laurindo [UNESP]; Mendes Fernandes, Alexandre Rodrigo (Inst Zootecnia, 2015)
Strategies to improve the nutritional aspects of beef, mainly the fatty acids composition, have become an important goal to the scientific community. The use of different oils sources could be an interesting device due its polyunsaturated fatty acids composition. The chemical and fatty acid composition of rump cap (Biceps femoris) from 35 Nellore young bulls finished at feedlot (96 days) were analyzed. These animals were fed a control diet with sugar cane and concentrate without oil or diets containing sugar cane and concentrate with different sources of oil (soybean or linseed), protected or not from ruminal degradation. A randomized block design was adopted with five treatments and seven replications. The means were compared using orthogonal contrasts at 0.05 significance level. Animals fed diets with oil showed higher levels (P<0.05) of protein and lower levels (P<0.05) of ash than control diet. Lower cholesterol (P<0.05) levels resulted from linseed oil added treatment compared to soybean oil (37.70 and 43.80 mg/100 g, respectively); on the other hand, cholesterol levels increased (P<0.05) for protected oils compared to non-protected (44.53 and 33.97 mg/100 g). Oil added diets resulted in higher (P<0.05) linolenic acid levels. Linseed oil increased (P<0.05) the levels of the fatty acids C14:1, C16:1 and C18:1 n9. Addition of linseed oil, whether protected or not, to the animal diets improves the fatty acid composition of the rump cap by increasing the amount of omega-3 fatty acids and improving the omega-6:omega-3 ratio.
Keywords: beef; cholesterol; fat; polyunsaturated fatty acids